Uncovering the Impact of Smartphone Addiction on Adolescent Emotion Regulation: A Systematic Literature Review for Intervention Strategies - Anita Dewi Astuti; Sunawan Sunawan; Ashari Mahfud (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to synthesize the impact of smartphone addiction on adolescent emotional regulation and identify effective intervention strategies. This article presents a Systematic Literature Review (SLR) following PRISMA guidelines, with searches conducted in Scopus, ScienceDirect, and Taylor & Francis for literature published between 2019 and 2024. After undergoing stages of identification, screening, feasibility, and inclusion, 11 articles that met the inclusion criteria were selected through a rigorous selection process. The research findings indicate that smartphone addiction correlates with increased psychological symptoms that negatively affect emotional regulation and social interaction among adolescents. This study highlights the need for multidimensional interventions, including Cognitive Behavioral Therapy (CBT), mindfulness, psychoeducation, and social support from parents and teachers. Although these approaches show promising results, evidence of long-term effectiveness remains limited, necessitating further research with a longitudinal design to assess sustainability. These findings also support the development of digital literacy interventions and school-based emotional regulation training to prevent smartphone addiction among adolescents, thereby supporting mental health and reducing the negative impacts of excessive technology use in the digital age. Keywords: smartphone addiction, emotion regulation, systematic literature review